Environmental context and contaminant biotransport by Pacific salmon interact to mediate the bioaccumulation of contaminants by stream‐resident fish. Issue 4 (6th March 2018) - Gerig, Brandon S.; Chaloner, Dominic T.; Janetski, David J.; Moerke, Ashley H.; Rediske, Richard R.; O'Keefe, James P.; de Alwis Pitts, Dilkushi A.; Lamberti, Gary A.
Abstract: The extent to which environmental context mediates the bioaccumulation of biotransported contaminants by stream‐resident organisms is poorly understood. For example, it is unclear the extent to which contaminant type, instream characteristics or resident fish identity interact to influence the uptake of contaminants deposited by Pacific salmon ( Oncorhynchus spp.) during their spawning runs. To address this uncertainty, we sampled four stream‐resident fish species from 13 watersheds of the Laurentian Great Lakes in locations with and without salmon runs across a gradient of instream and watershed characteristics. We determined the polychlorinated biphenyl (PCB) and mercury (Hg) concentration along with the stable isotope ratios for salmon and stream‐resident fish. We found that stream‐resident fish PCB concentrations were higher in reaches with salmon and were positively related to δ 15 N. In contrast, resident fish Hg concentrations were similar or lower in reaches with salmon compared with reaches lacking salmon and either exhibited a negative or no relationship with δ 15 N. Based on AICc, resident fish exhibited species‐specific PCB concentrations that were positively related to salmon PCB flux. Hg burdens exhibited an interaction between fish length and salmon Hg flux—as salmon Hg inputs increased, Hg levels decreased with increasing resident fish length. Because salmon eggs are enriched in PCBs but depleted in Hg, contaminant loads of resident fish appear to be driven by consumption of salmon eggs. We found no support for models that included the mediating influence of instream or watershed factors. Synthesis and applications . Our results highlight that contaminants bioaccumulate differently depending on contaminant type, species identity and the trophic pathway to contamination. Consequently, consideration of the recipient food web and route of exposure is critical to understanding the fate of biotransported contaminants in ecosystems. The transfer of contaminants by migratory organisms represents an understudied stressor in ecology. Effective management of biotransported contaminants will require the delineation of hotspots of biotransport and implementation of best management practices to reduce inputs of salmon‐derived pollutants. Abstract : Our results highlight that contaminants bioaccumulate differently depending on contaminant type, species identity and the trophic pathway to contamination. Consequently, consideration of the recipient food web and route of exposure is critical to understanding the fate of biotransported contaminants in ecosystems. The transfer of contaminants by migratory organisms represents an understudied stressor in ecology. Effective management of biotransported contaminants will require the delineation of hotspots of biotransport and implementation of best management practices to reduce inputs of salmon‐derived pollutants.